Penilaian Autentik Mata Pelajaran Pai Pada Kurikulum Merdeka Di SMAN 1 Sangatta Selatan - Sarwinda Rohmadani; Sulistia Wahyuningsih; Anjani Putri Belawati (CV. ITTC INDONESIA, 2024)
Even though authentic assessment has existed since the education unit curriculum, its implementation has not always been perfect. In addition, the independent curriculum places a strong emphasis on helping students develop their moral character. The term